Dinitrogen Activation: Dinitrogen Activation by Tricoordinated Boron Species: A Systematic Design (Adv. Theory Simul. 3/2020). Issue 3 (4th March 2020) - Rouf, Alvi Muhammad; Dai, Chenshu; Xu, Fangzhou; Zhu, Jun
Abstract : Dinitrogen activation is particularly challenging due to the inert nitrogen–nitrogen triple bond. In article number 1900205, Jun Zhu and co‐workers report that dinitrogen activation can be made thermodynamically and kinetically favorable through through the use of a metal‐free frustrated Lewis pair designed systematically from tricoordinated boron and N‐heterocyclic carbene species.